Strengthening English Language Proficiency Through Parent-Child Collaboration - Susanne I. Lapp (Asociación Colombiana de Profesores de Ingles, 2016)
The educationla system in the world today is facing incredible challenges as it attempts to educate young people to successfully compete in a global economy dominated by the English language. To support and encourage the efforts made by classroom teachers, parents are frequently being called on to take a more active role in their children's English language education (Huerta-Macias and Quintero, 1997). Educators and researchers recognize that the home environment plays a crucial role in the acquisition of literacy and children's success in the schools. Parents are being encouraged to participate in English literacy building activities with their children such as reading English stories and composing letters to help reinforce English skills which are taught in the schools.